Certification and Recertification in Welfare Programs: What Happens When Automation Goes Wrong? - Derek Wu; Bruce D. Meyer (Institute of Labor Economics (IZA), 2023)
How do administrative burdens influence enrollment in different welfare programs? Who is screened out at a given stage? This paper studies the impacts of increased administrative burdens associated with the automation of welfare caseworker assistance, leveraging a unique natural experiment in Indiana in which the IBM Corporation remotely processed applications for two-thirds of all counties. Using linked administrative records covering nearly 3 million program recipients, the results show that SNAP, TANF, and Medicaid enrollments fell by 15%, 24%, and 4% one year after automation, with these heterogeneous declines largely attributable to cross-program differences in recertification costs. Earlier-treated and higher-poverty counties experienced larger declines in welfare receipt. More needy individuals were screened out at exit while less needy individuals were screened out at entry, a novel distinction that would be missed by typical measures of targeting which focus on average changes overall. The decline in Medicaid enrollment exhibited considerable permanence after IBM's automated system was disbanded, suggesting potential long-term consequences of increased administrative burdens.
Keywords: H53; I38; 330; welfare programs; automation; take-up; targeting; administrative burdens